2019
DOI: 10.1016/j.jeurceramsoc.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Solid state reactions between SiC and Ir

Abstract: Reactivity between SiC and Ir as a function of SiC-crystallinity was investigated by diffusion bonding technique under a vacuum and over the temperature range of 1200-1450°C. As reaction products, various Irsilicides and free unreacted-C were detected. Reactivity is strongly affected by the temperature and SiCcrystallinity involving a series of interactions, from "no reaction" to "massive exothermic reactions". In particular, interfacial phenomena are more pronounced by the presence of defects and grain bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…The aforementioned studies mainly focused on the phase composition of the products. Camarano et al 25,26 have recently reported more details about the behavior of the Ir/SiC diffusion couple. No reaction between iridium and SiC was revealed in the 1200°C-1350°C temperature range; the first evidence of the reaction between hot-pressed SiC and Ir was detected only at 1375°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aforementioned studies mainly focused on the phase composition of the products. Camarano et al 25,26 have recently reported more details about the behavior of the Ir/SiC diffusion couple. No reaction between iridium and SiC was revealed in the 1200°C-1350°C temperature range; the first evidence of the reaction between hot-pressed SiC and Ir was detected only at 1375°C.…”
Section: Methodsmentioning
confidence: 99%
“…Another important finding was the formation of silicides with silicon content more than 50 at% (namely, Ir 4 Si 5 , Ir 3 Si 5 , and Ir 3 Si 4 ) in the immediate vicinity of SiC at 1450°C. 25,26 It was proposed that the formation of these silicide phases was possible due to silicon supersaturation at the boundary with SiC grains. It should be emphasized that Ir 2 Si silicide has never been detected as a product of the reaction between SiC and iridium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is logical to think that a SiC-IrSi X composite material will be a material with high resistance to oxidation. Previous studies by the authors have analyzed the compatibility of SiC with Ir [28] and the process of reactive infiltration of Si-Ir alloys in SiC-C porous preforms [29], where the infiltration process has been optimized, and SiC-IrSi 3 composite has been manufactured.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it is logical to think that a SiC / IrSiX composite material will be a material with a high resistance to oxidation. Previous studies of the authors have analyzed the compatibility of SiC with Ir [28] and the process of reactive infiltration of Si-Ir alloys in SiC-C porous preforms [29], where the infiltration process has been optimized, and SiC/IrSi3 composite has been manufactured.…”
Section: Introductionmentioning
confidence: 99%